Formação e trabalho no Movimento Sem Terra (MST): processos de resistência do campesinato - Antoniel Assis de Olivieira (2014)
The subjects peasants constituted an essential category in the Brazilian social formation. Since colonial times to the present day, the field was marked by conflicts, manipulations, deaths, resistors, achievements, etc., at different times of the performances of these subjects, there always fight over land. In the twentieth century began peasant organizations in the struggle for rights, including land reform, and to organize themselves according to their needs, these guys have created unions, parties, social movements, etc., in order to maintain greater coordination to strengthen their struggles. MST, which was constituted in the following decades one of the most significant social movements struggling for land and agrarian reform in the world - And so, in the wake of protests that occurred from the 1970s, the Landless Movement emerged. With objectives, internal organization and strategies of very sophisticated struggles allowed the MST adapt to varied moments the policy for this segment has experienced during its 30 years of existence. Thus, this research investigates two MST settlements of Minas Gerais, the processes of formation and job resources that qualify as the resistance of the subject field, especially residents of agrarian reform settlements, and to what extent change the mode life and work of these individuals. This is a qualitative research nature, whose investigative techniques used were structured interviews, participant observation and document studies of these communities. We opted to select individuals into groups with different functions in the structure of the MST, inquiring about the importance of training and work in the daily life of these subjects, as well as their tactics to the formation of other No Lands, aiming to identify if indeed possible changes found are due to the process undertaken by the MST. The analysis results showed the importance of the processes of formation of the MST for the awareness of people collectivize the perspective of the social relations of work / production, aiming to change the material conditions of life, humanizing them, and see the need to implement a field project in the interests of peasants. And yet, that changes in the relations of living and working result: the collectivized practices adopted from the beginning; targeted to meet the different demands of training Without Lands studies; the involvement of these people in demonstrations, meetings, meetings, seminars, trips, etc .; of school and non-school educational practices in settlements; the value given to productive work, especially into collectivization and cooperation of these practices - added to the "philosophy" of effective participation of the MST, among others. Thus, under the guidance of the MST, the resistance struggle within the Settlements, the acquisition of infrastructure as well as improving the conditions of life and work of these individuals are conditioned to the level of collective organization that is established, hence the importance of training in various aspects of life.